IMPROVING SHIP PASSENGER SATISFACTION BASED ON TICKET PRICE POLICIES AND CUSTOMER RELATIONSHIP MANAGEMENT THROUGH SERVICE QUALITY - Ninoy Octavines; Asep Suparman; Zaenal Abidin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Customer satisfaction is essential and determines the company's success, including customer loyalty, profitability, sales, and business performance. Therefore, this research focuses on efforts to reveal the effect of ticket price policies and customer relationship management (CRM) on passenger satisfaction by mediating service quality. The research used a survey method with a sample of 100 passengers of the Pioneer Ship of KM Belt Nusantara 76. The research instrument used to collect data was a questionnaire in the form of a Likert scale, and the results were analyzed using path analysis processed with Smart-PLS 4 software. The results show that ticket price policies, CRM, and service quality directly affect passenger satisfaction, ticket price policies and CRM directly affect service quality, and service quality significantly mediates the indirect effect of ticket price policies and CRM on passenger satisfaction. This evidence produces an empirical model about the effect of ticket price policies and CRM on ship passenger satisfaction through service quality. It not only provides a theoretical contribution to the development of transportation management science, particularly marketing management related to ticket pricing policies, CRM, service quality, and customer satisfaction, but also provides practical implications for shipping companies that manage pioneer ships, especially KM Sabuk Nusantara 76. Therefore, this empirical model can be used for discussion among academics, researchers, and practitioners before being adapted or adopted to increase passenger satisfaction in the future.